Lack of inducible nitric oxide synthases attenuates leukocyte–endothelial cell interactions in retinal microcirculation. Issue 5 (25th April 2008) - Iwama, D; Miyahara, S; Tamura, H; Miyamoto, K; Hirose, F; Yoshimura, N
Abstract : Aim: To investigate the effect of inducible nitric oxide synthases (iNOS) on inflammatory reactions during endotoxin-induced uveitis (EIU) in mice by studying leukocyte–endothelial cell interactions. Methods: EIU was produced in immunosuppressed iNOS −/− mice and C57BL/6 (normal) mice by footpad injection of lipopolysaccharide. Leukocytes were labelled with acridine orange. Leukocyte rolling in the retinal microcirculation was evaluated in vivo with acridine orange digital fluorography. The number of migrated leukocytes was counted in flat-mounted retina. Results: Both leukocyte rolling and migration peaked at 48 h after lipopolysaccharide injection. The maximal numbers of rolling leukocytes in the immunosuppressed iNOS −/− mouse retina decreased by 98.2% (p<0.001) compared with that in the normal mouse retina at 48 h after lipopolysaccharide injection. In addition, the maximal numbers of migrated leukocytes in the immunosuppressed iNOS −/− mouse retina decreased by 74.0% (p<0.001) compared with that in the normal mouse retina at 24 h after lipopolysaccharide injection. Furthermore, the diameters of major retinal veins of the immunosuppressed iNOS −/− group were smaller at both 24 and 48 h after lipopolysaccharide injection than were those of the normal group (p<0.001, respectively). Conclusions: A lack of iNOS suppresses leukocyte–endothelial cell interactions in the retinas of mice with EIU. This suggests that iNOS may play a role in the management of patients with uveitis and other inflammatory conditions.